Prekäre Vergemeinschaftung und verrückte Kämpfe: Repressive Integration als Herrschaftsmodus im prekären Dienstleistungsbereich - Artus, Ingrid (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2008)
Two case studies in multinational service enterprises (fast food and transport sector) show that strategies of corporate culture are quite efficient for management control of precarious and ’poor work’. The article discusses the problems of individual and collective interest representation within these special kind of employment relations, the reasons why struggles for respect and justice seem to be ’crazy conflicts’ there and in which context nevertheless occur ruptures in the system of absolute management control.